Dynamics of Human Pressures on the Mont Péko National Park (West-Côte d'Ivoire) - Ousmane Sidibe; Kouassi Kouadio Henri; Zadou Didie Armand; Kouame Djaha; Karidia Traore (European Scientific Journal, ESJ, 2018)
The Mont Péko national Park (MPNP) located to the West of Côte d'Ivoire underwent severe human pressure related to a succession of political and military crises from 2002 to 2011. Since 2013, the Ivoirians government is engaged in a process of rehabilitation of this park. This study aimed to evaluate the dynamics of human pressures from 1996 to 2018, in order to allow the manager of the park to better focus their awareness and protection activities. To achieve this, the RAPPAM method of WWF international was adopted for the collection of data. The study identified 10 types of pressures of which farm is the most severe followed by pressure on land, logging, bush fires, the establishment of settlements, poaching and pollution. The intensity of pressures on the MPNP doesn’t significantly vary depending on the areas, but this varies according to the socio-political gradient in time. The pressures have evolved gradually from 2002 to 2011 before beginning to decline progressively until 2018. Currently, except for uncontrolled bush fires, all pressures declined significantly, or even disappear for some. The existence of a variety of pressures on the MPNP to disturbing proportions is therefore related in part to the lack of monitoring during the crises. The anthropization of the MPNP found the springs of its acceleration in the existence of an armed gang who have organized, systematic exploitation of the resources.